2019
DOI: 10.1021/acs.jmedchem.9b01317
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of Necroptosis: Current Status and Perspectives

Abstract: Necroptosis, an important form of programmed cell death (PCD), is a highly regulated caspase-independent type of cell death that plays a critical role in the pathophysiology of various inflammatory, infectious, and degenerative diseases. Currently, receptor-interacting protein kinase 1 (RIPK1), RIPK3, and mixed lineage kinase domain-like protein (MLKL) have been widely recognized as critical therapeutic targets of the necroptotic machinery. Targeting RIPK1, RIPK3, and/or MLKL is a promising strategy for necrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 130 publications
0
60
0
Order By: Relevance
“…A better estimation of the oligomeric state of the MLKL executioner domain is hampered by the lack of structural information of MLKL inserted into micelles or the plasma membrane. Necroptosis could, in principle, be inhibited either by tackling the pseudokinase domain or the executioner domain of MLKL (7). Currently, two classes of compounds are reported to inhibit MLKL by covalently binding to Cys86 in the short α-helix 4 located on top of the four-helix bundle, which comprises α-helices 1, 2, 3, and 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better estimation of the oligomeric state of the MLKL executioner domain is hampered by the lack of structural information of MLKL inserted into micelles or the plasma membrane. Necroptosis could, in principle, be inhibited either by tackling the pseudokinase domain or the executioner domain of MLKL (7). Currently, two classes of compounds are reported to inhibit MLKL by covalently binding to Cys86 in the short α-helix 4 located on top of the four-helix bundle, which comprises α-helices 1, 2, 3, and 5.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, necroptosis has been associated with several inflammatory diseases, including amyotrophic lateral sclerosis (4), chronic intestinal inflammation (5), and skin inflammation (6). Therefore, all three proteins involved in the canonical necroptosis signaling and execution cascade (RIPK1, RIPK3, and MLKL) are attractive molecular targets for therapeutic small-molecule intervention (7).…”
mentioning
confidence: 99%
“…[66][67][68][69][70] Intriguingly, specific RIPK3 inhibitors such as GSK'840, GSK'843, and GSK'872 at high concentrations, despite their ability to inhibit necroptosis, favour the assembly of RIPK1/FADD/ caspase-8/FLIP L (complex IIb) leading to caspase activation and apoptosis. 71,72 In a rodent model of catalytically inactive RIPK3 D161N, mice could not survive through the embryonic period because of lethal caspase-8-mediated apoptosis. 73 Moreover, it was shown that blocking either RIPK3 or MLKL augmented the rate of apoptotic cell death in L-929 cells.…”
Section: Other Potential Interventions Against Necroptosis and Ripkmentioning
confidence: 99%
“…Recently, other pharmacological agents that interfere with RIPK3 have been identified such as diacerein, ponatinib, sorafenib and phenhydan 66‐70 . Intriguingly, specific RIPK3 inhibitors such as GSK'840, GSK'843, and GSK'872 at high concentrations, despite their ability to inhibit necroptosis, favour the assembly of RIPK1/FADD/caspase‐8/FLIP L (complex IIb) leading to caspase activation and apoptosis 71,72 . In a rodent model of catalytically inactive RIPK3 D161N, mice could not survive through the embryonic period because of lethal caspase‐8‐mediated apoptosis 73 .…”
Section: Introductionmentioning
confidence: 99%
“…[9] Following the necrostatins, several inhibitors of necroptosis were subsequently described over the last decade. [10] Representative examples are given in Figure 1. For instance, GSK has disclosed a chemical series of benzo [b] [1,4]oxazepin-4-one analogs [11] that proved to be effective anti-necroptosis agents.…”
Section: Introductionmentioning
confidence: 99%